Nonlinear Time Series Semiparametric and Nonparametric Methods - Gao, Jiti (Chapman & Hall, 2012)
During the past two decades or so, there has been a lot of interest in both theoretical and empirical analysis of nonlinear time series data. Models and methods used have been based initially on parametric nonlinear or nonparametric time series models. Such parametric nonlinear models and related methods may be too restrictive in many cases. This leads to various nonparametric techniques being used to model nonlinear time series data. The main advantage of using nonparametric methods is that the data may be allowed to speak for themselves in the sense of determining the form of mathematical relationships between time series variables. In modelling nonlinear time series data one of the tasks is to study the structural relationship between the present observation and the history of the data set.